Discourse of national clothes in kazakh and turkish proverbs - A.K. Akhmetbekova; E.A. Montanay; A. Koc (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы, 2024)
National clothing is not only the main indicator of the adaptation of each ethnic group to the environment, it also provides information about its lifestyle, tastes, ethics, and aesthetics. The clothes used in the composition of proverbs, as part of culture, reveal in the context the essence of linguistic and figurative thinking, which determines the cultural nature of the nation and forms the mentality of the people. As a component of proverbs, the names of the national clothing are an example of the interweaving of cultural images and linguistic images of the world in the context of concepts with their symbolic content and the discourse that arises on its basis.